1989
DOI: 10.1088/0953-8984/1/39/008
|View full text |Cite
|
Sign up to set email alerts
|

Hard-mode Raman spectroscopy and structural phase transition in the relaxor ferroelectric lead scandium tantalate, Pb(Sc0.5Ta0.5)O3

Abstract: The phase transition in the relaxor ferroelectric lead scandium tantalate, Pb(Sc0.5Ta0.5)O3, is investigated in both ordered and partly disordered (Sc, Ta disorder) modifications through the technique of hard-mode Raman spectroscopy. The vibrational modes for ordered para phase, ordered ferroelectric phase, disordered para phase and disordered ferroelectric phase are assigned to different representations of the respective groups (Fm3m (Z=2), R3m (Z=2), Pm3m (Z=1) and R3m (Z=1)) using the usual group-theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 20 publications
5
33
1
Order By: Relevance
“…7,14 It has been shown that T ? can be determined from the abrupt sharpening of the Raman peak near 240 cm À1 originating from off-centered B-site cations (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7,14 It has been shown that T ? can be determined from the abrupt sharpening of the Raman peak near 240 cm À1 originating from off-centered B-site cations (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Raman scattering, considering both possibilities, has been demonstrated on disordered and ordered forms of PST, respectively. 35 In the present paper, we analyze only cubic phases of the complex perovskite compounds. In other words, these are phases in which the oxygen compounds are synthesized at high temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13] Raman and IR spectroscopic studies of PST showed the increase in intensity and narrowing of the width of the phonon modes with increase in B-site chemical ordering. 14,15 The presence of Pb vacancies also strongly influences the structural and dielectric behavior of PST. It has been found that in disordered PST with Pb vacancies (PST-DV) the spontaneous relaxor-ferroelectric transition is suppressed and the compound shows only relaxor behavior.…”
Section: Introductionmentioning
confidence: 99%